The Effectiveness of Reproductive Innovations in Female Goats: A Qualitative Analysis of Productivity and Economic Sustainability in Goat Farming - Widiarta, I Putu Gede Didik; Adiputra, Kirana Dara Dinanti; Yuliyanti, Karenina Dwi; Fatmarischa, Novemia; Suhardi, Suhardi (Fakultas Peternakan Universitas Jambi, 2025)
Background: Goat farming in Indonesia plays a crucial role in enhancing rural incomes and improving food security. This study investigates the effectiveness of reproductive innovations, including artificial insemination (AI) and hormone synchronization, in boosting productivity and economic sustainability in goat farming. Purpose: This research aims to analyze the impact of artificial insemination (AI) and hormone synchronization on the reproductive efficiency of goats, to identify factors influencing the adoption of these technologies among small-scale goat farmers in Samarinda, Indonesia, and to determine the role of social capital in overcoming adoption barriers. Methods: This study uses a qualitative research approach with a survey method through in-depth interviews, focus group discussions (FGDs), and participatory observations. The sample consists of 15 small-scale goat farmers in Samarinda, Indonesia. Data were analyzed using thematic analysis to identify key challenges and benefits associated with the adoption of reproductive technologies. Results: The findings show that artificial insemination (AI) and hormone synchronization significantly increased reproductive efficiency, resulting in improved offspring production and reduced kidding intervals. However, adoption rates were constrained by high initial costs, limited technical support, and socio-economic barriers such as low education levels and restricted market access. Farmers who were part of cooperative networks achieved better outcomes, demonstrating the importance of social capital in overcoming adoption challenges. Conclusion: Based on the research findings, reproductive technologies have the potential to enhance goat farming productivity and economic sustainability. However, their successful implementation requires supportive policy interventions, including farmer training, improved access to resources, and strengthened market linkages to facilitate wider adoption.